The Russian urban sustainability puzzle : how can Russian cities be green? - Ermolaeva, Polina; Ermolaeva, Yulia; Basheva, Olga; Kuznetsova, Irina; Korunova, Valerya (Emerald points., 2021)
This book provides a comprehensive analysis of the socio-environmental issues and sustainability challenges facing Russian cities. It encompasses a three-year project in Moscow and Kazan which includes population surveys, mass-media analysis, and interviews with different groups of stakeholders. The authors offer extensive analysis of the main components of sustainable cities such as air and water quality, sustainable transport and mobility, energy efficiency and energy consumption, waste management, green and blue zones, environmental governance and politics. The conclusion provides critical reflections on how understandings of Russia's sustainability challenges can be used to build more tailored and effective environmental governance for its cities.